(x-2)(x-2)=40

Simple and best practice solution for (x-2)(x-2)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)(x-2)=40 equation:


Simplifying
(x + -2)(x + -2) = 40

Reorder the terms:
(-2 + x)(x + -2) = 40

Reorder the terms:
(-2 + x)(-2 + x) = 40

Multiply (-2 + x) * (-2 + x)
(-2(-2 + x) + x(-2 + x)) = 40
((-2 * -2 + x * -2) + x(-2 + x)) = 40
((4 + -2x) + x(-2 + x)) = 40
(4 + -2x + (-2 * x + x * x)) = 40
(4 + -2x + (-2x + x2)) = 40

Combine like terms: -2x + -2x = -4x
(4 + -4x + x2) = 40

Solving
4 + -4x + x2 = 40

Solving for variable 'x'.

Reorder the terms:
4 + -40 + -4x + x2 = 40 + -40

Combine like terms: 4 + -40 = -36
-36 + -4x + x2 = 40 + -40

Combine like terms: 40 + -40 = 0
-36 + -4x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '36' to each side of the equation.
-36 + -4x + 36 + x2 = 0 + 36

Reorder the terms:
-36 + 36 + -4x + x2 = 0 + 36

Combine like terms: -36 + 36 = 0
0 + -4x + x2 = 0 + 36
-4x + x2 = 0 + 36

Combine like terms: 0 + 36 = 36
-4x + x2 = 36

The x term is -4x.  Take half its coefficient (-2).
Square it (4) and add it to both sides.

Add '4' to each side of the equation.
-4x + 4 + x2 = 36 + 4

Reorder the terms:
4 + -4x + x2 = 36 + 4

Combine like terms: 36 + 4 = 40
4 + -4x + x2 = 40

Factor a perfect square on the left side:
(x + -2)(x + -2) = 40

Calculate the square root of the right side: 6.32455532

Break this problem into two subproblems by setting 
(x + -2) equal to 6.32455532 and -6.32455532.

Subproblem 1

x + -2 = 6.32455532 Simplifying x + -2 = 6.32455532 Reorder the terms: -2 + x = 6.32455532 Solving -2 + x = 6.32455532 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 6.32455532 + 2 Combine like terms: -2 + 2 = 0 0 + x = 6.32455532 + 2 x = 6.32455532 + 2 Combine like terms: 6.32455532 + 2 = 8.32455532 x = 8.32455532 Simplifying x = 8.32455532

Subproblem 2

x + -2 = -6.32455532 Simplifying x + -2 = -6.32455532 Reorder the terms: -2 + x = -6.32455532 Solving -2 + x = -6.32455532 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = -6.32455532 + 2 Combine like terms: -2 + 2 = 0 0 + x = -6.32455532 + 2 x = -6.32455532 + 2 Combine like terms: -6.32455532 + 2 = -4.32455532 x = -4.32455532 Simplifying x = -4.32455532

Solution

The solution to the problem is based on the solutions from the subproblems. x = {8.32455532, -4.32455532}

See similar equations:

| x(x+1)=x+x+1 | | t^2+8t=-15 | | .40(x-.5)=13 | | (z*z)+8z=-15 | | .25x-.666=.166 | | (t*t)-30t+29=0 | | (18+3)+(14+5)=(14+5)+(18+3) | | 28x-7y+13-18x-6-3y= | | 5x-14+2x=76 | | 37x-4=23 | | X=15000-.25x | | 52=13b | | q^2+6q+8=0 | | -2.5(g-8)-0.7g= | | -1/3( | | g(x)=8+2x+e^2x-6 | | f^1(x)=4x^3+3x^2+3x+3 | | f-1(x)=4x^3+3x^2+3x+3 | | f(x)=4x^3+3x^2+3x+3 | | 70+81+77(2x)=85 | | 70+81+77+2x=85 | | 3(5x+8)=3x-2 | | -3(3j-1)+5j-1=3j-2 | | -3(2c+3)+2c-4=-2c+1 | | -3(2z-1)+2z+1=3z+1 | | (.25)(2)+x=.60 | | -3(-3a+4)+4a-3=3a+2 | | X^2-9x-42=0 | | -3(2d+3)-4d+2=3d-2 | | X^2-9x-42=I | | -10w^2+17w-12=0 | | x*1.06=13000 |

Equations solver categories